DAMPAK KEBIJAKAN FISKAL REGIONAL TERHADAP OUTPUT DAN INFLASI DI KOTA BANDA ACEH - Eva Dayanti; Muhammad Nasir (Fakultas Ekonomi dan Bisnis UNSYIAH, 2016)
This research aims to know the impact of Regional Fiscal Policy between before and after the change of Qanun about Region Financial Management of Banda Aceh City towards its output and inflation. The research used qualitative descriptive and paired samples t test as its method. The result of the method showed that there is significant influence after the change of Qanun about Region Financial Management on GDRP, whereas no influence on inflation. From the results of the research, it can be concluded that magnitude impact of Regional Fiscal Policy of Banda Aceh can be seen from the level of PDRB and inflation, which is the level of GDRP is average larger after the change of Qanun about Region Financial Management of Banda Aceh City. Meanwhile the level of inflation average less after the change of Qanun about Region Financial Management of Banda Aceh City. Those results give an undertanding that Government Civil Servant expenditure, goods and services expenditure, and capital expenditure bring an influence on GDRP, but they do not bring influence on inflation. Therefore, the Government of Banda Aceh is expected to set the right and proper Fiscal Policy in order to increase the growth of sustainable economic.Penelitian ini bertujuan untuk melihat dampak kebijakan fiskal regional sebelum dan sesudah perubahan Qanun Pengelolaan Keuangan Daerah Kota Banda Aceh terhadap output dan inflasi di Kota Banda Aceh. Penelitian ini menggunakan metode deskriptif kualitatif dan paired sample t test. Hasil penelitian menunjukkan bahwa adanya pengaruh yang signifikan pada PDRB sesudah perubahan Qanun Pengelolaan Keuangan Daerah, sedangkan inflasi tidak ada pengaruh. Dari hasil penelitian dapat disimpulkan bahwa besaran dampak kebijakan fiskal regional Kota Banda Aceh dapat dilihat dari tingkat PDRB rata-rata lebih besar dan dan tingkat inflasi rata-rata lebih sedikit setelah dari perubahan qanun pengelolaan keuangan daerah Kota Banda Aceh. Hasil tersebut memberikan pengertian bahwa pengeluaran belanja pegawai, belanja barang dan jasa dan belanja modal memberikan pengaruh pada PDRB tetapi tidak pada inflasi. Untuk itu, diharapkan kepada pemerintah Kota Banda Aceh agar dapat menetapkan kebijakan fiskal yang tepat guna meningkatkan pertumbuhan ekonomi yang berkelanjutan.